Analysis of key components in the rehabilitation diagnosis of acute stroke patients - A. A. Shmonin; M. N. Mal’ceva; A. Oshchepkov; A. V. Starceva; A. R. Zashcherinskaya; M. S. Prosvirnina; P. V. Lebedev; D. D. Glistenkova; E. v. Mel’nikova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. There are key problems that limit patients’ functioning in the period after insult. The content of these problems determines the structure of multidisciplinary team.The objective of the study was to describe key problems that limited patients’ functioning in the period after insult and determine the structure of multidisciplinary team for resolving these problems efficiently.Material and methods. The study was observational. The sample size was 81 patients. Inclusion criteria: acute phase of post ischemic or hemorrhagic stroke (0–14 days after onset), mRs score 2 and more at admission to the hospital, the age over 18 years. Exclusion criteria: patients with transient ischemic attack, subarachnoid haemorrhage, Glasgow coma scale 2 and more at admission to the hospital. All patients – research participants received medical care in according to clinical guidelines, and multidisciplinary rehabilitation. In the course of rehabilitation, the first and second key problems that limited patients’ functioning in the period after insult were dedicated in each patient. We also investigated these problems and explored, which specialists must have been included in the structure of multidisciplinary team.Results. The key problems were non-medical in 24 % cases, poor exercise capacity were presented in 27 % cases, environment issues – 6 % cases, swallowing and speech disorders – 17 %, nursery problems – 4 %. The next specialists were needed to resolve the key problems: psychologist – 38 % cases, physical therapist– 69 % cases, occupational therapist – 28 % cases, neurologist – 27 % cases, physical medicine and rehabilitation physician – 27 % cases.Conclusion. Medical (rehabilitation physician, specialist, nurse) and non-medical specialists (occupational therapist, physical therapist, psychologist, logopaedist, etc.) must have been included in multidisciplinary team.